2004
DOI: 10.1165/rcmb.2003-0183oc
|View full text |Cite
|
Sign up to set email alerts
|

Apical and Basolateral ATP-Induced Anion Secretion in Polarized Human Airway Epithelia

Abstract: The present study investigated mechanisms underlying apical and basolateral P2Y(1)-mediated Cl(-) secretion in human airway epithelial cells. Apical and basolateral ATP induced short-circuit currents (I(sc)) with different properties via P2Y(1) receptors. The former comprised an immediate rise followed by a slow attenuation, whereas the latter was a transient rise with a higher peak and shorter duration (< 2 min). The actions of ATP were simulated by those of ADP, ADPbetaS, and ATPgammaS. Antagonists of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
(58 reference statements)
2
28
1
Order By: Relevance
“…Diverse responses to acute Nys challenge in Ussing chambers have been described in the literature. Although a pattern similar to the one we observed has been described in toad bladder A6 cells and rat colonic epithelium (13,25), other model systems (e.g., Calu-3 cells) responded to acute Nys exposure with a slower rise in I sc (10-20 min) and a plateau phase that was sustained for over 30 minutes (26,27). Since Nys binding to the plasma membrane is strictly dependent on sterol content (28), these differences might be attributed to differences in the apical membrane sterol composition in the different cell types studied.…”
Section: Discussionsupporting
confidence: 83%
“…Diverse responses to acute Nys challenge in Ussing chambers have been described in the literature. Although a pattern similar to the one we observed has been described in toad bladder A6 cells and rat colonic epithelium (13,25), other model systems (e.g., Calu-3 cells) responded to acute Nys exposure with a slower rise in I sc (10-20 min) and a plateau phase that was sustained for over 30 minutes (26,27). Since Nys binding to the plasma membrane is strictly dependent on sterol content (28), these differences might be attributed to differences in the apical membrane sterol composition in the different cell types studied.…”
Section: Discussionsupporting
confidence: 83%
“…Diadenosine pentaphosphate (Ap 4 A) increased [Ca 2ϩ ] i in HBE1 cells derived from human bronchial epithelial cells, probably acting via P2Y 2 receptors (Laubinger et al, 2001). Multiple P2Y receptor subtypes seem to be present on both apical and basolateral membranes of human airway-derived Calu-3 cells (Chambers et al, 2002), including P2Y 1 receptors (Son et al, 2004). UTP stimulates alveolar fluid clearance in the distal airspaces of rat lungs (Sakuma et al, 2004).…”
Section: Lung and Intrapulmonary Airwaysmentioning
confidence: 99%
“…Kolosova et al demonstrated that a long-lasting, nonhydrolyzed form of ATP (ATP␥S) given to mice after transtracheal administration of LPS prevented increases in bronchoalveolar lavage protein and white blood cell counts, Evans blue leakage into the lung, and decreased transendothelial cell electrical resistance (11). ATP has also been shown to induce anion secretion in airway epithelial cells and surfactant secretion in alveolar epithelial cells, both of which help to remove noxious particles from the lung (10,22,25). In addition, extracellular ATP appears to downregulate the human monocyte response to LPS through Tolllike receptor 4 (8).…”
mentioning
confidence: 99%